Comparison of Chemical Constituents of Essential Oils of Black Cumin (Nigella sativa L.) - Al Juhaimi1, Fahad; Figueredo2, Gilles; Musa Özcan3, Mehmet; Chalard4, Pierre (Asian Journal of Chemistry, 2013)
Essential oils from dried aerial parts of Nigella sativa were analyzed using gas chromatography-mass spectrometry (GC-MS). The air dried plant materials were subjected to hydrodistillation for 4 h using a Clevenger type apparatus to give yellow oils. The major compounds in the essential oil of Turkey sample were a-thujene (15.78 %), p-cymene (48.25 %), trans-4-methoxythujane (6.56 %), b-pinene (4.60 %), a-pinene (3.52 %) and limonene (2.88 %) while p-cymene (51.42 %), a-thujene (16.36 %), trans-4-methoxythujene (6.11 %), b-pinene (3.98 %), a-pinene (3.60 %) and limonene (2.84 %) were major components of Syria essential oil. The main compound of Ethiopia essential oil was p-cymene (55.03 %) followed by a-thujene (18.19 %), trans-4- methoxythujene (6.33 %), b-pinene (4.50 %), a-pinene (3.96 %) and limonene (2.85. %).